Violence Against Women, Hate and Law Perspectives from Contemporary Scotland - Barker, Kim.; Jurasz, Olga. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
"A shocking analysis of a deeply embedded problem (...). A brilliant piece of work. - Baroness Kennedy QC, UK "Recent attempts at law reform - both complete and incomplete - in Scotland have highlighted just how much work remains to be done in shaping the law's response to violence against women, both online and offline. Barker and Jurasz's work, with its breadth of focus, is a timely contribution to that debate." - Professor James Chalmers, University of Glasgow, UK This book presents the first academic study offering a holistic assessment of violence against women (VAW) in Scotland, both online and offline. In particular, it focuses on VAW, hate crime, and online forms of violence against women (OVAW). It critically assesses the gaps in the hate crime protections in Scots Law, focusing specifically on the absence of legal protections for VAW, OVAW, hate crime, and gender-based violence, and it includes international comparisons throughout. Given the current upsurge in the abuse of women, this book offers a holistic assessment of the phenomenon of VAW and makes the case for pressing law reform in Scotland, specifically for legal protections against VAW and OVAW to be included within Scots Law. The book contains not only research findings but also makes practical recommendations for law and policy reform in the areas of hate crime, VAW and OVAW. As such, it contributes to Scotland's progressive and leading approach to tackling violence against women and girls. Kim Barker is Senior Lecturer in Law at the Open University Law School, Open University, UK. Olga Jurasz is Senior Lecturer in Law at the Open University Law School, Open University, UK.
1. The 'Historical Curiosity' of Violence Against Women in Scotland -- 2 - (D)Evolved Policy-Making: Women and Scotland -- 3 - Scotland's History of Hate: From Public Order to Hate Crime and Back Again -- 4 - Gender and Hate: A Scottish Perspective -- 5 - Misogynistic Harassment -- 6 - Online Violence: A Blanket of Digital Sexism? -- 7 - Tackling VAW Through Scots Law: Alternative Proposals -- 8 - Conclusion: Towards Ending Violence Against Women.
Keywords: Critical criminology; Criminal law; Victims of crimes; Criminal behavior; Sex; Crime; Technology; Critical Criminology; Criminal Law and Criminal Procedure Law; Victimology; Criminal Behavior; Gender Studies; Crime and Technology